(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
This study aims to investigate the direct influence of distinctive capability and consumer requirements on value creation in private universities in the LLDIKTI Region II area. The method used is Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the relationship between these variables. The results showed that distinctive capability and understanding of consumer needs play an important role in improving value creation in higher education. The college’s distinctive capability has a positive impact on the institution’s image and attractiveness in the eyes of prospective students and stakeholders. In addition, by meeting consumer demands, universities can create higher value through innovation, superior services, and unique benefits. The findings provide a strong foundation for universities to focus on developing special capabilities and meeting consumer needs to improve marketing performance. This research makes a valuable contribution to understanding the factors that influence college marketing and provides guidance for strategic decision-making in educational institutions.